Octreotide improves burn-induced intestinal injury in the rat - (:unkn) unknown (ELSEVIER SCIENCE INC, 2003)
The local thermal trauma activates a number of systemic mediator cascades, e.g. a complement activation, cytokine production, resulting in a generalized sequestration and a priming of local and systemic neutrophils and macrophages. We aimed to determine the possible protective effect of octreotide (OCT), a synthetic somatostatin analogue, against burn-induced intestinal tissue damage possibly by inhibiting neutrophil infiltration. Under brief ether anaesthesia, shaved dorsum of the rats was exposed to 90 degreesC bath for 10 s to induce burn injury. Rats were decapitated either3,24 or 72 h after burn injury. Octreotide (10 mug/kg) or saline was administered subcutaneously (s.c.) immediately after the burn injury. In the 24- and 72-h burn groups, OCT injections were repeated three times daily. In the sham group the same protocol was applied except that the dorsum was dipped in a 25 degreesC water bath for 10 s Malondialdehyde (MDA) and glutathione (GSH) levels and myeloperoxidase (MPO) activity were determined in the intestinal tissue. The results demonstrate that burn injury results in significant neutrophil accumulation, as evidenced by increases in MPO activity. The increase in MDA and the concomitant decrease in GSH levels demonstrate the role of oxidative mechanisms in burn injury. OCT may have some beneficial therapeutic effects by reducing neutrophil-dependent injury and related lipid peroxidation following burn trauma. (C) 2002 Elsevier Science Inc. All rights reserved.
Keywords: burn; octreotide; myeloperoxidase; lipid peroxidation; glutathione; OXYGEN FREE-RADICALS; THERMAL-INJURY; BACTERIAL TRANSLOCATION; LIPID-PEROXIDATION; NEUTROPHIL ACTIVATION; HEMORRHAGIC-SHOCK; SOMATOSTATIN; INFLAMMATION; ISCHEMIA; THERAPY